2019
DOI: 10.21833/ijaas.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A note on thin-film flow of Eyring-Powell fluid on the vertically moving belt using successive linearization method

Abstract: The main goal of this work is to obtain the numerical solution for thin film flow of MHD an incompressible Eyring-Powell fluid on a vertically moving belt. The nonlinear equation governing the flow problem is modeled and then solved numerically by means of a successive linearization method (SLM). The numerical results are derived in tables for comparisons. The important result of this comparison is the high precision of the SLM in solving nonlinear differential equations. The solutions take into account the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Here successive linearization method (SLM) (Makukula et al, 2010a;2010b;Ahmed et al, 2015;Salah et al, 2019) is implemented to obtain the numerical solutions for nonlinear systems 8 and 10 corresponding to the boundary condition Eqs. 11-13.…”
Section: Procedures Of Computationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Here successive linearization method (SLM) (Makukula et al, 2010a;2010b;Ahmed et al, 2015;Salah et al, 2019) is implemented to obtain the numerical solutions for nonlinear systems 8 and 10 corresponding to the boundary condition Eqs. 11-13.…”
Section: Procedures Of Computationalmentioning
confidence: 99%
“…Recently some studies have presented a new method called Successive Linearization Method (SLM). This method has been applied successfully in many nonlinear problems in sciences and engineering, such as the MHD flows of non-Newtonian fluids and heat transfer over a stretching sheet (Shafiq et al, 2022), viscoelastic squeezing flow between two parallel plates, (Makukula et al, 2010a), two-dimensional laminar flow between two moving porous walls (Makukula et al, 2010b) and convective heat transfer for MHD boundary layer with pressure gradient (Ahmed et al, 2015), the thin-film flow of Eyring-Powell fluid on the vertically moving belt (Salah et al, 2019). Therefore, the effectiveness, validity, accuracy, and flexibility of the SLM are verified among all these successful applications.…”
Section: Introductionmentioning
confidence: 99%
“…Here successive linearization method (SLM) (Makukula et al, 2020b;Salah et al, 2019;Ahmed et al, 2015) is implemented to obtain the numerical solutions for nonlinear systems in Eqs. 8 and 10 corresponding to the boundary condition in Eqs.…”
Section: Procedures Of Computationalmentioning
confidence: 99%
“…Recently some studies have shown a new method called the successive linearization method (SLM). This method has been successfully applied to many non-linear problems in science and engineering, such as MHD flows of non-Newtonian fluids and transfer over a stretching sheet (Shateyi and Motsa, 2010), and the viscous pressure-flow between two parallel plates (Makukula et al, 2010a), a two-dimensional plate flowing between two porous walls (Makukula et al, 2010b), on the thin-film flow of Eyring-Powell fluid on the vertically moving belt (Salah et al, 2019) and convective thermal transfer heat to the MHD boundary layer with a pressure gradient (Ahmed et al, 2015). Therefore, this method has shown very high efficiency, accuracy, and flexibility of SLM in solving nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%
“…We used the Chebyshev pseudo-spectral approach to solve linear differential equations with higher-order deformation. The SLM methodology can be applied to highly nonlinear system boundary value problems as an alternative to more traditional numerical methods (see references [34][35][36][37][38][39][40][41]).…”
Section: Introductionmentioning
confidence: 99%